Resilient Learners: Experiences of Syrian Refugee Youth in Adult Education in Quebec - Calderon-Moya, Milagros; Sherab, Domenique; Maraj, Arianne; Ghosh, Ratna (The Canadian Journal for the Study of Adult Education / La revue canadienne pour l’étude de l’éducation des adultes, 2025)
Young adult Syrians who arrived in Canada with “disrupted education” in recent years are in a vulnerable position as they are transitioned into an education sector designed for independent and self‑directed adults. This study examines how the objectives and psychological well‑being of young adult Syrian refugees are supported in the adult education (AE) sector in Quebec. Specifically, how do they navigate the AE system to achieve their educational goals? How do they perceive the progress of their learning in the AE system? Data were collected from 10 Syrian students (18 to 24 years) through in‑depth individual and group interviews. Findings revealed that despite their strong self‑motivation and drive to achieve their educational goals, these students are vulnerable due to several factors—among them, the different methods of teaching in Syria, and unfamiliarity with independent teaching methods in AE in Quebec that make it difficult to navigate this new system, all while having to learn new languages.